HIV and AIDS in Africa: Christian reflection, public health, social transformation - Azetsop, Jacquineau (Orbis Books, 2016)
"HIV and AIDs both continue to spread in Africa and in some regions have become a threat to the very survival of nations. This book offers a number of perspectives on the crisis–theological, sociological, ecclesiological, public health, and more. It is a valuable resource for social analysis and theological reflection from an African perspective."–Page 4 of cover.